Cover Crops have Negligible Impact on Soil Water in Nebraska Maize–Soybean Rotation. (1st September 2018) - Barker, J. Burdette; Heeren, Derek M.; Koehler‐Cole, Katja; Shapiro, Charles A.; Blanco‐Canqui, Humberto; Elmore, Roger W.; Proctor, Christopher A.; Irmak, Suat; Francis, Charles A.; Shaver, Tim M.; Mohammed, Ali T.
Abstract : Core Ideas: The effect of cover crops on soil water storage for primary crops was evaluated. Field research was performed at sub‐humid and semi‐arid locations across Nebraska. Results indicate negligible impact of cover crops on soil water storage. Cover crop biomass was practically zero in west‐central Nebraska. One perceived cost of integrating winter cover cropping in maize ( Zea mays L.) and soybean [ Glycine max (L.) Merr.] rotation systems is the potential negative impact on soil water storage available for primary crop production. The objective of this 3‐yr study was to evaluate the effects of winter cover crops on soil water storage and cover crop biomass production following no‐till maize and soybean rotations. Locations were near Brule (west‐central), Clay Center (south‐central), Concord (northeast), and Mead (east‐central), NE. Treatments included crop residue only (no cover crop) and a multi‐species cover crop mix, both broadcast‐seeded before primary crop harvest and drilled following harvest. Pre‐harvest broadcast‐seeded cereal rye ( Secale cereale L.) was also included in the last year of the study because rye was observed to be the dominant component of the mix in spring biomass samples. Soil water content was monitored using neutron probe or gravimetric techniques. Mean aboveground cover crop biomass ranged from practically 0 to ∼3, 200 kg ha −1 across locations and cover crop treatments. Differences in the change in soil water storage between autumn and spring among treatments occurred in 4 of 20 location–rotation phase–years for the top 0.3 m of soil and 3 of 20 location–rotation phase–years for the 1.2‐m soil profile. However, these differences were small (<11 mm for the top 0.3 m and <26 mm for the 1.2‐m profile). In conclusion, winter cover crops did not have an effect on soil water content that would impact maize and soybean crop production.